2013
DOI: 10.3892/mmr.2013.1838
|View full text |Cite
|
Sign up to set email alerts
|

Function of inducible nitric oxide synthase in the regulation of cervical cancer cell proliferation and the expression of vascular endothelial growth factor

Abstract: Abstract. Inducible nitric oxide synthase (iNOS) is the key enzyme in NO synthesis and exhibits a high expression in numerous types of malignant tumors. Previous studies have demonstrated that iNOS promotes the production of tumor blood vessels by catalyzing the synthesis of additional NO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…The evidence of an interplay between mitochondrial and NADPH oxidase-derived ROS constitutes a feed-forward cycle in which mitochondrial ROS increase NADPH oxidase-dependent ROS production, that in turn increases mitochondrial ROS generation, in a sort of vicious cycle [ 14 ]. Oxidative stress driven by mitochondrial and/or Nox-mediated ROS generation activates the downstream-regulated inflammatory response of endothelial cells [ 16 , 59 , 65 ], inducing de novo CAM expression and secretion of inflammatory cytokines responsible for leukocyte recruitment and adhesion [ 9 ]. In PLC-treated skin flaps, ROS production was reduced and iNOS and NO level increased.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence of an interplay between mitochondrial and NADPH oxidase-derived ROS constitutes a feed-forward cycle in which mitochondrial ROS increase NADPH oxidase-dependent ROS production, that in turn increases mitochondrial ROS generation, in a sort of vicious cycle [ 14 ]. Oxidative stress driven by mitochondrial and/or Nox-mediated ROS generation activates the downstream-regulated inflammatory response of endothelial cells [ 16 , 59 , 65 ], inducing de novo CAM expression and secretion of inflammatory cytokines responsible for leukocyte recruitment and adhesion [ 9 ]. In PLC-treated skin flaps, ROS production was reduced and iNOS and NO level increased.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have demonstrated the links between Cav-1 and the angiogenesis that occurs in lung cancer. In Lewis lung carcinoma (LLC) cells (NSCLC cell line), cavtratin, the scaffolding domain peptide of Cav-1, can inhibit endothelial nitric oxide synthase (eNOS) function and subsequently block NO production, eventually to prevent LLC cells leakage and decrease angiogenesis [61,[65][66][67]. In Cav-1-knockout mice transplanted with LLC cells, the Cav-1 absence prevents VEGFR-2 from binding VE-cadherin (a protein that can interact with VEGFR-2 and lead to its dephosphorylation) and permits VEGFR-2 to be phosphorylated by other factors such as VEGF families, thus to enhance endothelial cell growth and lead to angiogenesis.…”
Section: Cav-1 and Angiogenesismentioning
confidence: 99%
“… 56 This explanation was corroborated by an iNOS knockdown experiment in HeLa cells that reduced their proliferation. 57 High NO concentrations impair the migration of neutrophil migration, which express receptors necessary for extricating tumor cells in cervical neoplasia. 57 NO also encumbers the success rate of conventional treatment therapy.…”
Section: Nitric Oxide In Various Cancersmentioning
confidence: 99%